Allosteric modulation of metabotropic glutamate receptor 4 activates IDO1-dependent, immunoregulatory signaling in dendritic cells. (March 2016) - Volpi, Claudia; Mondanelli, Giada; Pallotta, Maria T.; Vacca, Carmine; Iacono, Alberta; Gargaro, Marco; Albini, Elisa; Bianchi, Roberta; Belladonna, Maria L.; Celanire, Sylvain; Mordant, Céline; Heroux, Madeleine; et al.
Abstract: Metabotropic glutamate receptor 4 (mGluR4) possesses immune modulatory properties in vivo, such that a positive allosteric modulator (PAM) of the receptor confers protection on mice with relapsing-remitting experimental autoimmune encephalomyelitis (RR-EAE). ADX88178 is a newly-developed, one such mGluR4 modulator with high selectivity, potency, and optimized pharmacokinetics. Here we found that application of ADX88178 in the RR-EAE model system converted disease into a form of mild—yet chronic—neuroinflammation that remained stable for over two months after discontinuing drug treatment. In vitro, ADX88178 modulated the cytokine secretion profile of dendritic cells (DCs), increasing production of tolerogenic IL-10 and TGF-β. The in vitro effects required activation of a Gi -independent, alternative signaling pathway that involved phosphatidylinositol-3-kinase (PI3K), Src kinase, and the signaling activity of indoleamine 2, 3-dioxygenase 1 (IDO1). A PI3K inhibitor as well as small interfering RNA targeting Ido1 —but not pertussis toxin, which affects Gi protein-dependent responses—abrogated the tolerogenic effects of ADX88178-conditioned DCs in vivo . Thus our data indicate that, in DCs, highly selective and potent mGluR4 PAMs such as ADX88178 may activate a Gi -independent, long-lived regulatory pathway that could be therapeutically exploited in chronic autoimmune diseases such as multiple sclerosis. Highlights: ADX88178, a selective mGluR4 PAM, exerts long-term therapeutic effects in RR-EAE. ADX88178 activates a noncanonical mGluR4 signaling in DCs. ADX88178 induces a tolerogenic functional phenotype in DCs via immunoregulatory IDO1. Highly selective mGluR4 PAMs may represent novel drugs in chronic neuroinflammation.